1997
DOI: 10.4148/2378-5977.1945
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic and silage quality traits of forage sorghum cultivars in 1995 (1997)

Abstract: Agronomic and silage quality traits were measure d for 37 forage sorghum cultivars and three grain sorghum hybrids. The 1995 growing season was characterized by above average rainfall in the spring and early summer, and a hard freeze on September 22. At the time of the freeze, 20 cultivars had reached the early-milk to earlydough stage, 12 were in the bloom stage, and the remaining eight were still in the early-to late-boot stage . The late planting date and low plant populations resulted in below-normal whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…But Rox cultivar was in the statistically low NDF group. The two-year average of NDF ratio (51.2%) obtained in this study was similar to that of Siefers et al (1997) but it was lower than those reported by Millner et al (2011), Nazlı et al (2013 and Karadağ and Özkurt (2014), Delaying the harvest time of sorghum increases the ratio of cellulosic structures, a cell wall component. The differences among the NDF ratios reported by different researchers may be due to the differences in the ecologies of research areas, as well as the harvesting during different maturity periods.…”
Section: Ndf Ratiosupporting
confidence: 80%
“…But Rox cultivar was in the statistically low NDF group. The two-year average of NDF ratio (51.2%) obtained in this study was similar to that of Siefers et al (1997) but it was lower than those reported by Millner et al (2011), Nazlı et al (2013 and Karadağ and Özkurt (2014), Delaying the harvest time of sorghum increases the ratio of cellulosic structures, a cell wall component. The differences among the NDF ratios reported by different researchers may be due to the differences in the ecologies of research areas, as well as the harvesting during different maturity periods.…”
Section: Ndf Ratiosupporting
confidence: 80%
“…In this research, the lowest ADF ratios were determined Nutri Honey (36.64%) and Greengo (36.68%) cultivars, while the highest ADF ratios were found in Sugar Graze II (42.41%) and Rox (41.81%) cultivars (Table 3). In studies on sorghum, the ADF ratios were found to be 27.3-36.5% by Siefers et al (1997), 32.5-34.6% by Kozlowski (2006, 24.9-32.6% by Canbolat (2012), 34.1-40.1% by Tosunoglu (2014), 36.4-45.1% by Akdeniz et al (2003), 36.89-49.65% by Ozmen (2017), 30.1-37.4% by Kır and Dursun Şahan (2019). The difference between the ADF ratios obtained in this study and the ADF ratios in the other studies was probably related to the differences in cultivars used and ecologies of experimental sites.…”
Section: Resultsmentioning
confidence: 98%
“…Nutri Honey (56.51%) and Greengo (55.79%) cultivars had the lowest NDF ratios in this research (Table 3). In studies on sorghum, the NDF ratios were found to be 45.1-58.0% by Siefers et al (1997), 55.7-59.3% by Kozlowski (2006, 66.2-75.9% by Karadas (2008), 50.3% by Marsalis et al (2010), 46.6-55.9% by Canbolat (2012), 62.7-72.1% by Tosunoglu (2014, 62.5-74.0% by Akdeniz et al (2003), 55.81-76.11% by Ozmen (2017, 44.6-57.2% by Kir and Dursun Sahan (2019). The ADF and NDF ratios are the best indications of the energy capacity of a forage.…”
Section: Resultsmentioning
confidence: 98%
“…They established that the fresh forage yield was 80 t with the total DM of 19.3 t ha -1 . Through a study carried out, with 37 sorghum cultivars, Siefer and Bolsen (1997) explained that DM and DM yield ranged between 23-39% and 990-1080 kg ha -1 , seed yield was approximately at 24 kg ha -1 . When chemical characteristics of fresh sorghum taken into account the findings were in agreement with the results reported by Sonon and Bolsen (1996).…”
Section: Resultsmentioning
confidence: 99%